Colorimetric Detection of Hg(II) Ion Using Silver Nanoparticles Capped with 3-Hydroxybenzoic Acid - Gusrizal Gusrizal; Andi Hairil Alimuddin; Ajuk Sapar; Rizki Noviani Ridwan; Sri Juari Santosa (Molekul, 2019)
In this paper, we report for the first time thesimple method for detection of Hg(II) ion in anaqueousmedium using silver nanoparticles capped with 3-hydroxybenzoic acid. Silver nanoparticles capped with 3-hydroxybenzoic acid were preparedby reduction of the silver ion with 3-hydroxybenzoic acid and without surface functionalization. The formation of silver nanoparticles was characterized by a UV-Visible spectrophotometer. The yellowcolloid of prepared silver nanoparticles capped with 3-hydroxybenzoic acid showed a surface plasmon resonance peak at 420 nm. The ability of silver nanoparticles capped with 3-hydroxybenzoic acid in detection was tested by doing a reaction with several metal ions individually(Na(I), K(I), Cu(II), Zn(II), Ca(II), Mg(II), Hg(II), Mn(II), Ni(II), Pb(II), and Co(II)). It was foundthat silver nanoparticles capped with 3-hydroxybenzoic acid highly selective toHg(II) and then the prepared silver nanoparticles were developedfor detection of Hg(II) ion. Addition of 1 mL Hg(II) ion into 4mL the as-preparedsilver nanoparticles reducedthe peak of surface plasmon resonance spectra, andthe reduction of peak intensity was proportional to the concentration of Hg(II) ion. A goodlinear relationship (R2= 0.998) between absorbance at 420 nm and concentrationof Hg(II) over the range 1.0x10-3to 5.5x10-3M was obtained. Silver nanoparticles capped with 3-hydroxybenzoic acid were highly sensitive to Hg (II) ion with the detection limit down to 4.7x10-5M. Application the method to the real water sample showed the excellentresult with recovery ranged from 98 to 101%. The proposed method was found to be useful forthe colorimetric detection of Hg(II) ion in an aqueousmedium.